Is bilingualism protective for adults with aphasia?. (2nd March 2020) - Dekhtyar, Maria; Kiran, Swathi; Gray, Teresa
Abstract: The bilingual advantage proposes that bilingual individuals have enhanced cognitive control compared to their monolingual counterparts. Bilingualism has also been shown to contribute to cognitive reserve by offsetting the behavioral presentation of brain injury or neural degeneration. However, this effect has not been closely examined in individuals with post-stroke or post-TBI aphasia. Because bilingualism has been suggested as a factor of cognitive reserve, it may provide protective mechanisms for adults with aphasia. In the current study, evidence for the bilingual advantage was examined in 13 Spanish-English bilingual healthy adults (BHA) compared to 13 English monolingual healthy adults (MHA). Additionally, evidence for cognitive reserve as defined by a bilingual advantage was examined in 18 Spanish-English bilingual adults with aphasia (BAA) compared to 18 English monolingual adults with aphasia (MAA) who were otherwise matched on their age, education, language impairment, and non-verbal executive functions. All participants completed a non-linguistic cognitive control task that included congruent and incongruent conditions. Results indicated no bilingual cognitive control advantage on reaction times in healthy adult groups; however, BAA were faster than MAA, suggesting that bilingualism may contribute to cognitive reserve in adults with aphasia. Thus, manipulating multiple languages throughout the lifetime may be protective after an acquired brain injury. Highlights: Bilingual and monolingual healthy adults and adults with aphasia completed a non-linguistic cognitive control task. Results revealed no bilingual cognitive control advantage in healthy adult groups. Results revealed that bilingual adults with aphasia were more efficient on this task than monolingual adults with aphasia. These findings suggest bilingualism may contribute to cognitive reserve in adults with aphasia.